PWE-055 Coeliac Disease is More Common in Subjects with Postural Orthostatic Tachycardia Syndrome Compared to Healthy Controls. (17th August 2016) - Penny, HA; Aziz, I; Ferrar, M; Atkinson, J; Hoggard, N; Hadjivassiliou, M; West, JN; Sanders, DS
Abstract : Introduction: Patients with the postural tachycardia syndrome (PoTS) have anecdotally reported symptom improvement on a gluten-free diet (GFD) but there has been no association study between PoTS and coeliac disease. Therefore, we aimed to evaluate the prevalence of coeliac disease and self-reported gluten sensitivity in a cohort of patients with PoTS and compare this with local population data. Methods: 100 PoTS patients were recruited from the syncope clinic to complete a validated questionnaire which screened for gluten sensitivity and related symptoms. Case notes were reviewed for relevant GI diagnoses. For comparison, the local coeliac prevalence was determined from a total of 1200 controls (Control Group 1) and a further 400 controls (Control Group 2; frequency matched for age and sex) filled out the same questionnaire. Results: Four out of a hundred (4%) patients with PoTS had serology and biopsy-proven coeliac disease. This was significantly higher than the prevalence of coeliac disease in Control Group 1 (12/1200, 1%; OR 4.1, 95% CI 1.3 to 13.0; p = 0.02). In comparison with Control Group 2, patients with PoTS had a higher prevalence of self-reported gluten sensitivity (42% versus 19%; p < 0.001), coeliac disease (4% versus 1%; p = 0.04) and IBS (36% versus 9%; p < 0.0001). Conclusion: There is a high prevalence of coeliac disease and self-reported gluten sensitivity in patients with PoTS. We advocate screening for the gluten-related disorders in patients with PoTS. Further studies are required to ascertain the nature of this relationship. Disclosure of Interest: None Declared